T lymphocyte–specific deletion of SHP1 and SHP2 promotes activation-induced cell death of CD4 + T cells and impairs antitumor response - Connor J. R. Foster; Jasper Du; Oscar Pundel; Mitchell J. Geer; Ryan C. Ripert; Jia Liu; Taylor A. Heim; Kiyomi Y. Araki; Amanda W. Lund; Jun Wang; Benjamin G. Neel (Proceedings of the National Academy of Sciences, 2025)
SHP1 (PTPN6) and SHP2 (PTPN11) are closely related protein-tyrosine phosphatases (PTPs), which are autoinhibited until their SH2 domains bind paired tyrosine-phosphorylated immunoreceptor tyrosine-based inhibitory/switch motifs (ITIMs/ITSMs). These PTPs bind overlapping sets of ITIM/ITSM-bearing proteins, suggesting that they might have some redundant functions. By studying T cell–specific single and double knockout mice, we found that SHP1 and SHP2 redundantly restrain naïve T cell differentiation to effector and central memory phenotypes, with SHP1 playing the dominant role. Surprisingly, loss of SHP2 alone in T cells enhanced the antitumor effects of anti-PD-1 antibodies, whereas there was no effect of SHP1 deletion. Also unexpectedly, the absence of both PTPs resulted in poorer tumor control and failure to respond to Programmed Cell Death Protein 1 (PD-1) blockade, associated with reduced frequency and activation of T cells and dendritic cells. Mechanistic studies revealed that CD4 + , but not CD8 + , T cells lacking SHP1 and SHP2 show increased activation-induced cell death upon anti-CD3/CD28 stimulation. Adoptive transfer of antigen-specific CD4 + T cells restored normal levels of tumor control in mice lacking both PTPs. Together, our results demonstrate that SHP1 or SHP2 is required to prevent activation-induced cell death of CD4 + T cells and is critical for tumor immunity, raising the possibility that inhibition of SHP2 might augment the therapeutic efficacy of PD-1-based immune therapy.